Impostors tending to the wild: Purposes of authorship analysis and a specific impostors method in the Karvounakis terrorism case - Clarke, Isobelle; Grant, Tim (Language and Law / Linguagem e Direito, 2025)
On 11th January 2018, an improvised explosive device was discovered in Princes Street Gardens in Edinburgh. Almost a month later, a journalist received an email which linked to a blog post on a Mexican eco-extremist website. This blog post claimed responsibility for the bomb. This paper describes the provision of linguistic expert evidence in this case, which included an authorship profile, a cross-genre authorship verification, and a comparative authorship analysis. Each authorship analysis was for a different purpose and that purpose guided the type of analysis selected. For the final authorship analysis, we developed a new method inspired by the General Impostors Method, which we call the Specific Impostors Method. After describing this method and its application to this case we conclude with our reflections on the Specific Impostors Method and the outcomes of the case.